Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Solve the following for [tex]y[/tex]:

[tex]\[8x + 3y = 6\][/tex]

[tex]\[y =\][/tex]


Sagot :

To solve the equation [tex]\(8x + 3y = 6\)[/tex] for [tex]\(y\)[/tex], we will isolate [tex]\(y\)[/tex] on one side of the equation. Here are the steps:

1. Start with the given equation:
[tex]\[ 8x + 3y = 6 \][/tex]

2. Subtract [tex]\(8x\)[/tex] from both sides to begin isolating [tex]\(y\)[/tex]:
[tex]\[ 3y = 6 - 8x \][/tex]

3. Divide every term by 3 to solve for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{6 - 8x}{3} \][/tex]

4. Simplify the right-hand side:
[tex]\[ y = \frac{6}{3} - \frac{8x}{3} \][/tex]

5. Perform the division in each term:
[tex]\[ y = 2 - \frac{8x}{3} \][/tex]

So, the solution for [tex]\(y\)[/tex] in terms of [tex]\(x\)[/tex] is:
[tex]\[ y = 2 - \frac{8x}{3} \][/tex]